The Influence of Financial Literacy and Peer Conformity on Student Consumptive Behavior - Murniati, Murniati; Sardiana Sardiana; Novitasari Novitasari (STKIP Taman Siswa Bima, 2024)
Good financial literacy is important for students to ward off negative consumer behavior. Knowledge of financial literacy makes students able to manage the influence of peers to make wise financial decisions. This research aims to determine the influence of financial literacy and peer conformity on student consumption. The research method used was a survey. The population is 128 Economic Education students at Dayanu Ikhsanuddin University, with engineering stratified random sampling 58 respondents were selected as samples. The data collection technique uses a questionnaire. Data was tested using linear regression analysis and coefficient of determination. The results of the research show 1) the influence of financial literacy on student consumptive behavior is 0.055, meaning that financial literacy has a 5.5% influence on student consumptive behavior and the rest is influenced by other factors, 2) the influence of peer conformity on student consumptive behavior is 0.235, meaning that peer conformity Peers have a 23.5% influence on students' consumptive behavior. 3) The value of the closeness of the relationship between the financial literacy variable and the peer conformity variable is 0.351, meaning that the two variables have a positive linear relationship. 4) the relationship between the two variables is significant, 0.007 <0.05, so it can be said that the variables financial literacy and peer conformity are lowly correlated, 5) the influence of financial literacy and peer conformity on student consumptive behavior is 0.240, meaning that financial literacy and peer conformity have an effect of 24% on student consumptive behavior.